PENGARUH KUALITAS PRODUK DAN KEPERCAYAAN PELANGGAN TERHADAP KEPUASAN PELANGGAN PADA PT PAL INDONESIA (PERSERO) SURABAYA MELALUI KEPUTUSAN PEMBELIAN - Anang Sudi Ahmadi; Wasis Budiarto; Mei Indrawati (Prodi Magister Manajemen Universitas Wijaya Putra, 2017)
The potential of the domestic shipyards market in serving the shipbuilding industry and also to contribute or supply marine transportation is very large market opened, it can be seen by high sea transport demand for domestic/local sea transportation and international as well. Competition between shipyards on shipbuilding industry is also tight increasingly, so it becomes a new challenge and demands for each shipyard to be able to keep loyal customers or seize the new market accordingly. Therefore, strategic steps are quite needed by each shipyard to survive and compete in the shipping business industry. The purpose of this study is to describe and analyze the influence of variables to the customers loyalty of PT PAL Indonesia. This research uses explanatory research, quantitative approach with path analysis by using SPSS tool software. Population in this research is entire customer PT PAL Indonesia Persero Surabaya with total 60 companies/agencies. Results of analysis and hypothesis proved that direct or indirect was giving positive results which means it found significant influence accordingly.